MELK is a prognostic biomarker and correlated with immune infiltration in glioma - Yang, Haiyan; Zhou, Huandi; Wang, Guohui; Tian, Lei; Li, Haonan; Zhang, Yufeng; Xue, Xiaoying (Frontiers in Neurology, 2022)
Objective: Glioma accounts for the vast majority of primary brain tumors with inevitable recurrence and poor prognosis. Maternal embryonic leucine zipper kinase (MELK) is overexpressed in multiple human tumors and could activate a variety of oncogenic associated signal pathways. However, its role in glioma microenvironment is still largely unknown. Methods: We collected the RNA sequence data and clinical information of gliomas from the Chinese Glioma Genome Atlas (CGGA), The Cancer Genome Atlas (TCGA), and the Gene Expression Omnibus (GEO) databases, and investigate MELK expression and its correlation with clinicopathologic features and prognosis in glioma. Moreover, the relationship between MELK expression and immune cell infiltration in the tumor microenvironment of gliomas was explored though Single-sample gene set enrichment Analysis (ssGSEA) and CIBERSORT. In addition, Gene set enrichment analysis (GSEA) analysis and Metascape online analysis were performed to find out the signaling pathways enriched by differentially expressed genes (DEGs) between MELK high and low expression groups. Finally, immunohistochemistry was performed to validate our findings. Results: Data analysis of CGGA and GEO datasets showed that MELK was significantly upregulated in gliomas than in normal brain tissues, and MELK expression was obviously correlated with clinical pathologic features, including age, WHO grade, histological subtype, IDH mutant status, 1p19q codeletion status and PRS type. Stratified analysis, Cox regression analysis and nomogram model revealed that high expression of MELK predicted poor survival, and could serve as an independent prognostic biomarker for glioma. Moreover, results from enrichment pathways analysis indicated that immune system process, angiogenesis, apoptosis, cell cycle and other oncogenic related signal pathways were significantly enriched between MELK high and low expression groups. Immune infiltration analysis demonstrated that increased MELK expression was significantly correlated with higher immune scores, higher fraction of immunocytes (T cells, NK cells resting, Macrophages, Mast cells resting, and Neutrophils) and higher expression levels of immune checkpoints (B7-H3, CTLA4, LAG3, PD-1, PD-L1, and TIM3). Finally, immunohistochemistry analysis validated our findings that high expression of MELK relates to increased malignancy and poor prognosis of glioma. Conclusion: Our findings identified that MELK could act as an independent prognostic indicator and potential immunotherapy target for glioma.